Regulation of Circadian Behavior by Astroglial MicroRNAs in Drosophila. Issue 3 (1st March 2018) - You, Samantha; Fulga, Tudor A; Van Vactor, David; Jackson, F Rob
Abstract: You et al . describe the first genome-wide analysis of glial microRNAs in the context of circadian behavior. They identified multiple miRNAs whose manipulation... We describe a genome-wide microRNA (miRNA)-based screen to identify brain glial cell functions required for circadian behavior. To identify glial miRNAs that regulate circadian rhythmicity, we employed a collection of "miR-sponges" to inhibit miRNA function in a glia-specific manner. Our initial screen identified 20 glial miRNAs that regulate circadian behavior. We studied two miRNAs, miR-263b and miR-274, in detail and found that both function in adult astrocytes to regulate behavior. Astrocyte-specific inhibition of miR-263b or miR-274 in adults acutely impairs circadian locomotor activity rhythms with no effect on glial or clock neuronal cell viability. To identify potential RNA targets of miR-263b and miR-274, we screened 35 predicted miRNA targets, employing RNA interference-based approaches. Glial knockdown of two putative miR-274 targets, CG4328 and MESK2, resulted in significantly decreased rhythmicity. Homology of the miR-274 targets to mammalian counterparts suggests mechanisms that might be relevant for the glial regulation of rhythmicity.